Efektivitas latihan otot dasar panggul terhadap kepuasan seksual pada pasangan usia subur - Sriwenda, Djudju; Sudiapermana, Elih; Pramudia, Joni Rahmat; Yanti, Yulidar; Purnamasari, Ira (Holistik Jurnal Kesehatan, 2025)
Background: Obesity is associated with decreased sexual satisfaction, loss of sexual desire, impaired sexual performance, and reluctance to engage in sexual contact. These things will affect household harmony if not addressed. Overcoming sexual dissatisfaction can be done with pharmacological and non-pharmacological techniques. Performing pelvic floor muscle exercises is one non-pharmacological method that can be done as an alternative to improve sexual dissatisfaction. Purpose: To determine the effect of the effectiveness of pelvic floor muscle exercises on sexual satisfaction in fertile couples. Method: Quasi-experimental design with a pre-test and post-test approach using a control group. Sampling was carried out by purposive sampling and obtained 54 respondents with inclusion criteria aged 35-45 years, married > 10 years, and number of children ≥ 2. The sexual satisfaction instrument used was the Sexual Satisfaction Index Form (SSIF) and data analysis used the Wilcoxon and Mann-Whitney tests. Results: Based on the Mann-Whitney Test, it shows that the median rating of sexual satisfaction in normal BMI obtained a score of 29.63 and in excessive BMI obtained a score of 25.80 with a p-score of 0.378. Meanwhile, the median rating of increased sexual satisfaction in normal BMI obtained a score of 29.10 and in excessive BMI obtained a score of 26.22 with a p-score of 0.502. Based on the Wilcoxon Test, the comparison of pre-post test between normal and excessive BMI obtained a p-score <0.001. Conclusion: Fertile couples with normal and excessive BMI had increased levels of sexual satisfaction before and after doing pelvic floor muscle exercises for 20 minutes every day for 4 weeks (p<0.001). In addition, between normal BMI and excessive BMI there was no significant effect on increasing sexual satisfaction (p>0.005). Suggestion: Pelvic floor muscle exercises are recommended to be done routinely as a non-pharmacological therapy to increase sexual satisfaction.   Keywords: Obesity; Pelvic Floor Muscle Exercises; Sexual Satisfaction.   Pendahuluan: Obesitas dikaitkan dengan penurunan kepuasan seksual, hilangnya hasrat seksual, gangguan kinerja seksual, dan keengganan untuk melakukan kontak seksual. Hal-hal tersebut akan berdampak pada keharmonisan rumah tangga jika tidak diatasi. Mengatasi ketidakpuasan seksual dapat dilakukan dengan teknik farmakologi dan non farmakologi. Melakukan latihan otot dasar panggul merupakan salah satu cara non farmakologi yang dapat dilakukan sebagai alternatif dalam memperbaiki  ketidakpuasan seksual. Tujuan: Untuk mengetahui pengaruh efektivitas latihan otot dasar panggul terhadap kepuasan seksual pada pasangan usia subur. Metode: Desain quasi eksperimen dengan pendekatan pre-test dan post-test menggunakan kelompok kontrol. Pengambilan sampel dilakukan secara purposive sampling dan didapatkan sebanyak 54 responden dengan riteria inklusi adalah usia 35-45 tahun, lama menikah > 10 tahun, dan jumlah anak ≥ 2. Instrumen kepuasan seksual yang digunakan adalah Sexual Satisfaction Index Form (SSIF) dan analisis data menggunakan uji Wilcoxon dan Mann-Whitney. Hasil: Berdasarkan Mann-Whitney Test menunjukkan bahwa median rank kepuasan seksual pada IMT normal mendapatkan skor 29.63 dan pada IMT berlebih mendapatkan skor 25.80 dengan p-skor 0.378. Sementara itu, median rank peningkatan kepuasan seksual pada IMT normal mendapatkan skor 29.10 dan pada IMT berlebih mendapatkan skor 26.22 dengan p-skor 0.502. Berdasarkan Wilcoxon Test perbandingan pre-post-test antara IMT normal dan berlebih mendapatkan p-skor <0.001. Simpulan: Pasangan usia subur dengan IMT normal dan berlebih memiliki tingkat kepuasan seksual yang meningkat sebelum dan setelah melakukan latihan otot dasar panggul durasi 20 menit setiap hari selama 4 minggu (p<0.001). Selain itu, antara IMT normal dan berlebih tidak memiliki pengaruh yang signifikan terhadap peningkatan kepuasan seksual (p>0.005). Saran: Latihan otot dasar panggul direkomendasikan dilakukan secara rutin sebagai terapi non farmakologis untuk meningkatkan kepuasan seksual.   Kata Kunci: Kepuasan Seksual; Latihan Otot Dasar Panggul; Obesitas.